Pendidikan Prenatal Yahudi dan Relevansinya dengan Pendidikan Islam - Mivtahul Kasana; Anggraeni Novita Sari (Academica : Journal of Multidisciplinary Studies, 2017)
This article attempts to analyze the relevance of Jewish prenatal education to Islamic education. This research uses descriptive-analysis method with content analysis approach on the book "Dismantle the Brilliant Jewish Learning Methods" by Delvi Luhvian. To enrich the analysis, the authors also conducted a study of literature on media and articles that related to research problems. The results of this study indicate that the Jews believe that the learning process of children is started since in the womb. Therefore, the Jews are very concerned about prenatal education. In a Jewish perspective, prenatal education is done to stimulate emotional ability by listening to music, inviting fetuses and humming, they also stimulate the intellectual ability by reading books and learning mathematics. Jewish prenatal education is also relevant to Islamic education which also emphasizes prenatal education, but in Islamic perspective, prenatal education not only training the emotional and intellectual abilities but also spiritual abilities.Keywords:prenatal education, Islamic, Jewish